Development and reproduction of Chrysoperla externa (Neuroptera: Chrysopidae) fed with Neotoxoptera formosana (Hemiptera: Aphididae) - COSTA, MARLICE B.; BEZERRA, CARLOS E. S.; SOUZA, BRÍGIDA; SOARES, CRISTIANA S. A.; SILVA, MARISE (Revista Colombiana de Entomología, 2012)
We evaluated biological and reproductive aspects of Chrysoperla externa fed with the aphid Neotoxoptera formosana reared on Welsh onion (Allium fistulosum). The experiment was conducted at a temperature of 25 ± 1 °C, RH 70 ± 10% and photophase of 12 hours, with 40 repetitions of one individual for the larval period. For the adults, nine pairs were used, fed with diet composed of brewer’s yeast and honey (1:1). We observed duration of 14.1 days, with survival of 75.0% for the larval period, and 9.6 days with 96.7% survival for the cocoon (pre-pupa + pupa), with a total survival of 72.5% in 23.7 days of post-embryonic development. Regarding the adults, males and females showed an average survival probability of 39.9 and 52.1 days, respectively, and the average production of eggs per female was 741.1 eggs, with 74.6% hatchability. It is concluded that N. formosana is a viable food source for C. externa and that further studies should be conducted to evaluate the potential of this predator in IPM programs for Welsh onion.